2021
DOI: 10.1186/s12879-021-06013-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and CT features of mild-to-moderate COVID-19 cases after two sequential negative nucleic acid testing results: a retrospective analysis

Abstract: Background The clinical and imaging features of patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections that progressed to coronavirus disease 2019 (COVID-19) have been explored in numerous studies. However, little is known about these features in patients who received negative respiratory nucleic acid test results after the infections resolved. In this study, we aim to describe these features in a group of Chinese patients. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Chest radiological imaging, which had slower recovery rate ( Rong et al, 2021 ), still showed fibrotic-like changes on more than 1/3 of severe patients with COVID-19 after 6 months ( Han et al, 2021 ), and therefore, in our analysis, this outcome was found to be significantly better after 10 days on chest x-ray and 14-15 days on computerized tomography imaging. This suggested a favorable outcome in the long term for favipiravir groups.…”
Section: Discussionmentioning
confidence: 47%
“…Chest radiological imaging, which had slower recovery rate ( Rong et al, 2021 ), still showed fibrotic-like changes on more than 1/3 of severe patients with COVID-19 after 6 months ( Han et al, 2021 ), and therefore, in our analysis, this outcome was found to be significantly better after 10 days on chest x-ray and 14-15 days on computerized tomography imaging. This suggested a favorable outcome in the long term for favipiravir groups.…”
Section: Discussionmentioning
confidence: 47%
“…Currently, three approaches, i.e., reverse-transcription polymerase chain reaction (RT-PCR), serological/immunological antigen-based tests and chest computed tomography (CT), are generally used for COVID-19 diagnosis ( Lukas et al, 2020 ; Udugama et al, 2020 ; Valera et al, 2021 ). Of the above, chest CT is a key screening tool for patients with COVID-19 symptoms ( Cai et al, 2020 ; Rong et al, 2021 ). Despite being widely available in cities, CT facilities typically do not reliably detect COVID-19 infection in its early stages, making them unsuitable for intensive patient surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients have a fever (91.3%) and cough (76 %), similar to another study that reported that 93.3% of cases had a fever and 86.1% had a cough. Another study reported admission symptoms of mild-to-moderate cases which is in contrast to a Bangladesh study that included many non-critical patients who had a fever (79%), weakness (68%), cough (45%), altered sensation of taste or smell (35%), headache (32%) and body ache (32%) (Rong et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…A chest CT scan was frequently used in the diagnosis and disease prognosis of COVID-19 (Ai et al, 2020;Dey et al, 2020;Islam et al, 2020). The COVID-19 diagnosis involves a combination of epidemiological history, clinical manifestations, early chest CT examinations, and RT-PCR, with a particular emphasis on definite epidemiological history and early chest CT findings when positive RT-PCR tests lag, or test results are negative but clinically positive signs are shown (Ai et al, 2020;Rong et al, 2021). Only a few studies were conducted on a limited number of chest CT image findings among Bangladeshi COVID-19 patients (Biswas et al, 2021;Clump et al, 2020).…”
Section: Introductionmentioning
confidence: 99%